Enhancing agricultural resilience in smallholder farmers in Ghana - Baamonyor, Abdul-latif; Abera, Wuletawu; Mponela, Powell; Akpatsu, Isaac Boatey; Masoud, Jalaludeen (2023)
The Excellence in Agronomy Ghana GAIP use case aims to fortify agricultural sustainability and resilience, placing a strong emphasis on improving livelihoods of smallholder farmers. By employing a BASKET-A (Bundled Advisory Services Kits for Enabling Transformation Solutions for Agronomy) approach, which combines insurance with agroadvisory services encompassing fertilizer recommendations, cropping calendars, and good agronomic practices, this initiative has demonstrated remarkable enhancements in the productivity, profitability and climate resilience of smallholder farmers compared to traditional farming practices.